MINIMIZING RESIDUAL STAND DAMAGE AND FELLING COST USING LOWEST POSSIBLE FELLING TECHNIQUE (A case study in one logging company in West Kalimantan) - Suhartana, Sona; Krisdianto, Krisdianto (Secretariat of Forestry Research and Development Agency, 2005)
The implementation of felling technique in logging companies is not yet carried out efficiently and appropriately. Study on the lowest possible felling technique (LPFf) is considered to be important to reduce residual stand damage and felling cost. This study was carried out in a logging company in West Kalimantan in 2004. The aim of this study was to determine the effect of LPFT on residual stand damage and felling cost. Data collected in this research include: residual stand damage, working time, timber volume, productivity, efficiency, stump height and felling cost. Two categories data were analyzed with respect to their possible differences using T-test. The result showed that the implementation of LPFT was more advantage impact compared to that of conventional felling technique, which is indicated by the following factors: (1) Trees damage decreased 2.96%; (2) Poles damage decreased 4.75%; (3) Felling productivity decreased 17.16%; (4) Felling efficiency increased approximately 3.2%; (5) Felling cost increased about Rp 327.07 / m; and (6) in average stump height was 40.60 cm lower.